Pengembangan Modul Pembelajaran Radiasi Benda Hitam Berbasis Saintifik terhadap Kemampuan Berpikir Kritis Siswa - Arjuna Suha; Neng Nenden Mulyaningsih; Irnin Agustina Dwi Astuti; Popi Purwanti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
This research develops scientific-based learning on black body radiation material, knows the feasibility of scientific-based learning modules, and sees student responses to scientific-based learning modules. Provide alternative teaching materials that can be used in physics learning. Learning can be easily done because the learning steps that are already in the module can be a solution for teachers and students learning physics does not look difficult and boring. The limited trial results obtained an average score of 3.2 or 80% in the "good" category and based on the results of the trial, it was obtained an average of 3.21 or 80% in the "good" category. These results can be ignored that the physics learning module with a scientific approach to black body radiation material is suitable for use in learning at school